AGENCY THROUGH BODILY ALTERITY: THE CASE OF “PRO-ANOREXIA” WEBSITES - Kleyn, Megan; Clark, Jude (PINS-Psychology in Society, 2025)
The phenomenon of pro-anorexia websites is beginning to receive attention within the academy following its increasing visibility in popular media. Pro-Ana is vibrant, yet subversive online community, with membership purportedly comprised of girls in their mid to late teens. This article draws on an Honours research project that explored discursive representation on two such websites. It draws on post-structuralist feminist theoretical resources, and discourse analysis to explore the constructions of identity and bodily inscriptions within the Pro-Ana community. We include a brief statement on historical constructions of anorexia, as well as more contemporary medical and lay representations. Our main analysis focuses on a generic logo of the websites, which reads “anorexia is a lifestyle not a disease”. We argue that members of the Pro-Ana community (Anas) display agency by both resisting and conforming to dominant discursive representations of anorexia, problematizing dominant constructions of the gendered body. We posit that this performativity is a critical reply to the medical and public responses to the anorexic body and the phenomenon of Pro-Ana.